Kyrle's disease presenting in an extensive distribution along lines of Blaschko - Rajesh Verma; Biju Vasudevan; Sunita Kakkar; Pratibha Mishra; Vijendran Pragasam; Disha Dabbas (Wolters Kluwer Medknow Publications, 2015)
A 24-year-old lady presented with the complaints of asymptomatic dark, raised lesions over her body since past 4 years. Dermatological examination revealed hyperkeratotic, hyperpigmented papules in a Blaschkoid distribution over trunk and extremities. The hyperkeratotic lesions could be removed leaving behind a small crater. Skin biopsy revealed hyperkeratosis, parakeratosis with epidermal invagination, focal cornified plug with basophilic degenerated material and dyskeratotic keratinocytes. Dermis showed dilated capillaries with moderate amount of perivascular lymphocytic infiltrate and granulomatous lymphocytic infiltrate in the deep dermis. A diagnosis of Kyrle's disease was made and patient was started on oral acitretin 25 mg daily with satisfactory response to therapy. This is the first reported instance of Kyrle's disease occurring in an extensive Blaschkoid distribution.